The Implementation of Early Childhood Education within Curriculum 2013 - Wahyuningsih, Sri; Haryani, Eka (Indonesian Journal of Early Childhood Education Studies, 2015)
Early Childhood Curriculum 2013 is a set of an institution learning planning which through a scientific approach. This curriculum concerns to all of the development aspects such as spiritual aspect, behavior, knowledge, and also a skill. Those aspects are related and be one to each other in a learning activity in central class which are applied according to the theme which is chosen before. The theme is as flexible as children need; for example of what TKIT Bina Amal Semarang had done, the theme was about Semarang’s food. This research described the implementation of early childhood education’s curriculum 2013 in TKIT Bina Amal Semarang and also factors which supported it. This research was a naturalistic qualitative research and used observation, interview and also documentation methods, interactive data analysis technique, and triangulation validity technique. Based on the implementation of curriculum 2013 data analysis in TKIT Bina Amal Semarang through a scientific approach. There were some process of this approach; process I: observing (involving all of their senses abilities), process II: asking (being critic on what they observed), process III: collecting information, process IV: associating (connecting old knowledge with the new one), and process V: communicating (QA or Question-Answer section). It was applied according to the theme which was close to them. Supporting factors of this implementation in TKIT BinaAmal were 1) the capability of educators (mostly were bachelor degree graduates) 2) institution (they were institution which supports to improve children education), 3) facilities and infrastructure (learning media in each center), educative games tools, outdoor games tools which were comfortable), 4) supporting activities (painting, coloring, computers, abacus’ and lassy).     The conclusion of this research was the implementation of early childhood education’s curriculum 2013 through scientific approach included observing, asking, collecting information, associating, and communicating. This implementation was supported by some factors. There were the capability of educators, institution, facilities and infrastructure and also APE.How to citeWahyuningsih, S. & Haryani, E. (2015). The Implementation of Early Childhood Education within Curriculum 2013. Indonesian Journal of Early Childhood Education Studies, 4(2), 81-85. doi:10.15294/ijeces.v4i2.9460DOI 10.15294/ijeces.v4i2.9460